2016
DOI: 10.1002/jcu.22412
|View full text |Cite
|
Sign up to set email alerts
|

Sonohysterosalpingography: Comparison of foam and saline solution

Abstract: HyFoSy allows a more accurate diagnosis of tubal patency compared with HyCoSy. © 2016 Wiley Periodicals, Inc. J Clin Ultrasound 45:67-71, 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 20 publications
1
14
0
Order By: Relevance
“…Among the four pregnant women, two experienced intrauterine hysteroscopy (one had operative hysteroscopy for U3 uterine anomaly; and one had hysteroscopy for G1 fibroid) performed at least 12 months prior to the ART cycle. Since it is well-known that an increase in pregnancy outcome is achieved in the 3-6 months following hysteroscopy, we would like to underline that in our patients a correlation between the increase in pregnancy outcome and hysteroscopy was thus avoided (Neerja and Jain, 2014;Di Spiezio Sardo et al, 2016;Piccioni et al, 2017;Riganelli et al, 2018).…”
Section: Discussionmentioning
confidence: 92%
“…Among the four pregnant women, two experienced intrauterine hysteroscopy (one had operative hysteroscopy for U3 uterine anomaly; and one had hysteroscopy for G1 fibroid) performed at least 12 months prior to the ART cycle. Since it is well-known that an increase in pregnancy outcome is achieved in the 3-6 months following hysteroscopy, we would like to underline that in our patients a correlation between the increase in pregnancy outcome and hysteroscopy was thus avoided (Neerja and Jain, 2014;Di Spiezio Sardo et al, 2016;Piccioni et al, 2017;Riganelli et al, 2018).…”
Section: Discussionmentioning
confidence: 92%
“…Therefore, attention should be given to the three-dimensional ultrasound examination of the uterine cavity shape. 14 Unreasonable operation during radiography would also cause misdiagnosis. 15 When the balloon is filled and becomes too large, or the position of the balloon is too high, the resistance of the bolus injection of contrast agent would be increased, and the contrast agent would not be able to flow outward smoothly.…”
Section: Discussionmentioning
confidence: 99%
“…74 A small observational study compared HyFoSy and HyCoSy to laparoscopy, and found HyFoSy to be superior with 94.4% concordance with laparoscopy (sensitivity of 87.5% and specificity of 100%), while HyCoSy showed concordance with laparoscopy in 57.8% (sensitivity of 50% and specificity of 66.6%). 75 The preliminary results of the FOAM study show that HyFoSy and HSG have a concordance of 85%. 52 Furthermore, a diagnostic accuracy study compared air/saline HyCoSy, HyFoSy, and HyFoSy with high-definition flow (a bidirectional Doppler feature) with the gold standard of laparoscopy with dye.…”
Section: Sensitivity and Specificity And Reliability Of Tubal Patencmentioning
confidence: 93%